A research about psychosocial and economic burdens in the families of alcohol and heroin addicts - Gümüş, Ömer; Şahin, Emre; Top, M. Şerif (Journal of Dependence, 2002)
Objective: In this research, the relation between duration and level of addiction and the psychological problems experienced related to drug and alcohol usage is studied. Additionally, the objective is to compare groups of alcohol and drug addicts by studying psychosocial and economic burden on their families, the reactions and behaviors of family members to them, the development path of their addiction, and their level of knowledge about how to fight against addiction and get cured. Method: The experiment group consists of 40 alcohol addicts identified as “Alcohol Addict” according to DSM- IV diagnostic rules and 40 members of their relatives and also 40 heroin addicts identified as “Heroin Addict” according to DSM-IV diagnostic rules and 40 members of their relatives as well, summing up to total 80 addicts and 80 members of addicts’ relatives. Demographic data form, Michigan Alcoholism Screen Test–MAST and Questionnaire For Family Burden- QFB are applied to experiment group. Results: It is observed that alcohol addiction starts later than heroin addiction and alcohol addicts refer to clinics more lately than heroin addicts for medication (year mean=34.6±6.9 and 22.9±4.8, t=8.66, p<0.001). Comparing to the alcohol addicts, heroin addicts do not have a regular job (x²=23.16, p<0.001) and social insurance (x²=23.900, p<0.001). Due to longer penitentiary experience (x²=17.28, p<0.001), more frequent suicidal attempts (x²=5.95, p< 0.05) and show more harmful behaviors (x²=14.90, p<0.001) to themselves than alcohol addicts and it is observed that it increases the psychosocial and economic load of heroin addicts on their families more than alcohol addiction case (t=2.71, p<0.01). Conclusion: It is observed that heroin addiction cause more psychosocial and economic load on both family and society than alcohol addiction. We can conclude that the burden and pressure on family members will alleviate, therefore, the rehabilitation of addicts will be sustained within family environment as well if families get informed sufficiently about addiction during the ongoing process of medication.